Peran Klan dalam Pemilihan Kepala Kampung Tahima Soroma, Jayapura - Rosita P. Aronggear; Agustina Ivonne Poli; J. R. Mansoben (Universitas Cenderawasih, 2020)
The encounter of regulations originating from the state with the culture of indigenous peoples has given birth to a new socio-cultural order. Like what happened in Pulo Village, during the election process for the village head, there was a negotiation process between state regulations and customary norms. For this reason, using an ethnographic approach, this study seeks to uncover how the role of clans in the election of village heads is related to the system of social stratification with relations between kin. The technique of selecting informants is determined purposively, with the data collection techniques used are observation and interviews. Data analysis includes data reduction processes, data descriptions and conclusions. The results showed that the social stratification of the Kayupulo people consisted of, Ondoafi, clan head Clans (upper class), Clan Members, and Migrant Communities. Then relations between clans are formed from economic activity and clan relations in exogamous marriages. The role of kin in the election of village heads is seen starting from the process of determining candidates for candidates through a process of customary consolidation that those who verify that they can nominate as village chiefs. Clans that were reclaimed as village leaders are carried out in turn from lines, Sibi, Yowe, Haay, and Soro for every one time tenure.